2018
DOI: 10.1016/s0140-6736(17)33308-1
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophins versus clomifene citrate with or without intrauterine insemination in women with normogonadotropic anovulation and clomifene failure (M-OVIN): a randomised, two-by-two factorial trial

Abstract: The Netherlands Organization for Health Research and Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…It is envisioned that the hydrogen bonds between the enriched -OH, -NH 2 , C]O/CONH 2 groups in CDs and the carboxyl/ hydroxyl groups in CC, as well as the polar interactions between them form stable electrons donor-acceptor adducts, the efficient energy transfer statically quenches the uorescence of CDs. In the case of static quenching process, the number of binding site (n) and the binding constant (K) can be obtained according to eqn (2) (Fig. 10b)…”
Section: Fluorescence Quenching Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is envisioned that the hydrogen bonds between the enriched -OH, -NH 2 , C]O/CONH 2 groups in CDs and the carboxyl/ hydroxyl groups in CC, as well as the polar interactions between them form stable electrons donor-acceptor adducts, the efficient energy transfer statically quenches the uorescence of CDs. In the case of static quenching process, the number of binding site (n) and the binding constant (K) can be obtained according to eqn (2) (Fig. 10b)…”
Section: Fluorescence Quenching Mechanismmentioning
confidence: 99%
“…1) is the rst and the most widely used pharmaceutical capable of promoting ovulation in female patients with polycystic ovary syndrome and therefore treating infertility. 1,2 However, a lot of clinical reports have shown that an excessive dosage of CC in the human body also causes ovarian hyperstimulation syndrome and luteinized unruptured follicle syndrome. Hence, the sensitive and reliable monitoring of CC is crucial in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published multi‐centre Dutch RCT compared gonadotrophins with timed intercourse or intrauterine insemination (IUI) versus clomiphene citrate with timed intercourse or IUI over six cycles in 666 infertile WHO Group 2 anovulatory women with CCF and found a higher live‐birth rate (52% vs 41%; relative risk 1.24; 95% CI 1.05–1.46; P = 0.0124) and reduced time to conception leading to live birth (5.0 vs 5.5 months; P = 0.028) favouring gonadotrophins and the addition of IUI did not increase live births compared with timed intercourse. There was no evidence of a difference in multiple pregnancy rates …”
Section: Pharmaceutical Ovulation Induction Treatmentsmentioning
confidence: 92%
“…Women should also be advised if the use of such agents is off-label (though permitted) in countries where this is the case 145 . Women who have achieved regular ovulation with oral induction agents can continue this treatment for up to 12 months, as pregnancy and complication rates are acceptable for this time period 151 . However, prolonged use of ovulation induction agents should be avoided owing to low success rates 145 A second-line treatment for women who fail to respond to oral induction agents is gonadotrophins, which are injectable drugs 152 , .…”
Section: [H2] Ovulation Disordersmentioning
confidence: 99%